2014
DOI: 10.1111/jce.12508
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Sympathetic Tone by Recording Subcutaneous Nerve Activity in Ambulatory Dogs

Abstract: Introduction We tested the hypothesis that subcutaneous nerve activity (SCNA) of the thorax correlates with the stellate ganglion nerve activity (SGNA) and can be used to estimate the sympathetic tone. Methods and Results We implanted radiotransmitters in 11 ambulatory dogs to record left SGNA, left thoracic vagal nerve activity (VNA) and left thoracic SCNA, including 3 with simultaneous video monitoring and nerve recording. Two additional dogs were studied under general anesthesia with apamin injected into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 24 publications
2
60
0
Order By: Relevance
“…Similar to a prior report in normal canines, 8 all seven dogs demonstrated subcutaneous nerve discharges with similar morphology to the signals recorded from the left stellate ganglion. In addition, SCNA morphology was similar to filtered skin and muscle sympathetic nerve activity obtained in microneurography studies.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Similar to a prior report in normal canines, 8 all seven dogs demonstrated subcutaneous nerve discharges with similar morphology to the signals recorded from the left stellate ganglion. In addition, SCNA morphology was similar to filtered skin and muscle sympathetic nerve activity obtained in microneurography studies.…”
Section: Resultssupporting
confidence: 87%
“…In the present study, the presence of SCNA was demonstrated in all seven dogs using widely spaced bipolar electrodes placed in the upper trunk. Similar to that in normal dogs, 8 SCNA in these diseased dogs had similar morphology, onset and duration compared to SGNA, but the recordings were sufficiently different to eliminate significant cross talk between the channels. In addition, SCNA signals were similar to filtered human microneurography signals obtained directly from a peripheral nerve.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations